IMPLEMENTASI MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) - Imadduddin Abas (UNISAN JURNAL, 2024)
The writer tries to formulate the problem as follows: "How to implement Contextual Learning in Fiqh subjects at MTs AL Huda Karang Melati Kecamatan Semendawai Timur Kabupaten Oku Timur Amal, Gedung Meneng District, Tulang Bawang Regency. Contextual Teaching Learning. (2). To describe student learning outcomes after contextual learning is carried out at MTs AL Huda Karang Melati Kecamatan Semendawai Timur Kabupaten Oku Timur. This research is a qualitative research to describe the factors that become obstacles for teachers who teach fiqh subjects with the application of Contextual Learning at MTs AL Huda Karang Melati Kecamatan Semendawai Timur Kabupaten Oku Timur District, Tulang Bawang Regency. This research includes descriptive research, namely research that describes the conditions in the field as they are. Model as an example of learning (objects, teachers, students and others). The inhibiting and supporting factors in Contextual Teaching and Learning (CTL) learning in fiqh learning are the presence of some students who are still reluctant to express their opinions, and To support contextual learning can run optimally Teachers are expected to be able to improve the quality of learning by providing experience contextual and practical learning to students